Bipolarna artroplastika s steblom HP 2 v oskrbi zlomov stegneničnega vratu - Andoljšek, Matej (Zdravniški vestnik, 2003)
Background. In General Hospital Jesenice we started with arthroplasties in patients with a fracture of the femoral neck in 1985. At the beginning cemented stems were used. In 1991 modular self-tapping uncemented stem (HP 1; first generation) was introduced. Two years later bipolar head was added. In 1994 second generation of modular selftapping uncemented stem (HP 2) came intouse. In prospective study, early clinical results of bipolar arthroplasty with HP 2 stem in patients with a fracture of the femoral neck are evaluated. Methods and results. From 1994 to 1999, 332 fractures of the femoral neck wereoperated. Two hundred and thirtyfour prostheses were implanted, and of these, 123 were bipolar with HP-2 stem (one third of all patients). Patients were on average 78 years old, and women outnumbered men five to one. After an average hospital stay of three weeks, 80% of patients were able to ambulate; in 20% of patients rehabilitation failed. 88% of patients retained their preinjury social status. Hospital mortality was 4.4%. Complications were rare,and ended with reoperation in eleven patient, seven for early and four for late complications (two deep infections, two material failures; 3.5%). With minimal follow-up of two years, there was only one aseptic loosening of the HP 2 stem. Conclusions. This prospective study of early clinical results shows, that bipolar arthroplasty with a modular self-tapping uncemented stem (HP 2) is usefull mode of treatment in patients with a fracture of the femoralneck.
Keywords: Arthroplasty; Artroplastika; Femoral Neck Fractures; Femur, vrat, zlomi; Hip Prosthesis; Kolčni sklep, proteza; Surgery; Treatment Outcome; Zdravljenje, izid